2013
DOI: 10.1007/s11084-013-9326-5
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Ions are More Effective than Sodium Ions in Salt Induced Peptide Formation

Abstract: Prebiotic peptide formation under aqueous conditions in the presence of metal ions is one of the plausible triggers of the emergence of life. The salt-induced peptide formation reaction has been suggested as being prebiotically relevant and was examined for the formation of peptides in NaCl solutions. In previous work we have argued that the first protocell could have emerged in KCl solution. Using HPLC-MS/MS analysis, we found that K+ is more than an order of magnitude more effective in the L-glutamic acid ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…55 This kind of catalytic activity was also found for sodium and potassium ions, 29 but the systematic study of the influence of pH, temperature, and metal concentration on the polymerization of glycine revealed a negative influence of other divalent metals. 62 , which have virtually no influence.…”
Section: Prebiotic Synthesis By Homogeneous Catalysismentioning
confidence: 80%
See 1 more Smart Citation
“…55 This kind of catalytic activity was also found for sodium and potassium ions, 29 but the systematic study of the influence of pH, temperature, and metal concentration on the polymerization of glycine revealed a negative influence of other divalent metals. 62 , which have virtually no influence.…”
Section: Prebiotic Synthesis By Homogeneous Catalysismentioning
confidence: 80%
“…It was namely demonstrated that in 1 M concentration, they catalyse polymerization of glutamic acid with 1,1'-carbonyldiimidazole into 9-(Na + ) and 11-mer (K + ) oligopeptides. 29 More important, however, is that simple dipeptides Ser-His and Gly-Gly (less efficiently) catalyse polymerization of amino-acid esters, peptide fragments, and building blocks of peptide nucleic acids (PNA). 30 Basic peptides, polymers of lysine, catalyse hydrolysis of phosphodiester bond, especially if their conformation is β-sheet rather than random coil.…”
Section: Oparin's Solution: Homogeneous Catalysis In Coacervate Dropletsmentioning
confidence: 99%
“…The formation of oligomers of the amino acid L-Glu in aqueous solutions induced through sodium and potassium salts during the activation of growth with CDI condensing agent has been previously examined [8]. The results showed that the dependence of the oligomer chain distribution in length ( means the number of monomers in the oligomer) depends on the type of solution (where = Na, K, O with sodium and potassium ions and without ions, resp.)…”
Section: Introductionmentioning
confidence: 99%
“…For a model abiogenic peptide formation reaction, 1,1'‐carbonyldiimidazole was proposed as an efficient dehydration agent . Recently, we have reported that potassium chloride has more than an order of magnitude greater catalytic effect than the same concentration of sodium chloride on amino acid condensation in aqueous solution with carbonyldiimidazole . Interestingly, peptides obtained by different model reactions with amino acid mixtures conserve several sequence motifs (i.e.…”
mentioning
confidence: 99%
“…Peptides synthesized in experiments of abiogenic peptide formation are not likely to occur in the existing databases so the only way to their identification by MS/MS spectra is de novo sequencing. [15,23] Previously, using UV-LC and MS analysis we have shown that potassium ions have more than an order of magnitude greater catalytic effect than sodium ions in a reaction of peptide formation with carbonyldiimidazole, [6] but no detailed structural characterization was done. Here we present a mass spectrometric study of carbonyldiimidazolecatalyzed oligomerization of glutamic acid in different environments: with 1 M sodium or potassium chloride and without salts.…”
mentioning
confidence: 99%